A Pilot Trial of Topical Capsaicin Cream for Treatment of Cannabinoid Hyperemesis Syndrome. (20th July 2020) - Dean, Diana J.; Sabagha, Noor; Rose, Kaitlin; Weiss, Alexander; France, John; Asmar, Timothy; Rammal, Jo‐Ann; Beyer, Margaret; Bussa, Rebecca; Ross, Jacob; Chaudhry, Kaleem; Smoot, Thomas; et al.
Abstract: Objectives: Patients with cannabinoid hyperemesis syndrome (CHS) present frequently to the emergency department. Previous case studies suggest dramatic symptomatic improvement with topical capsaicin treatment. This exploratory study examined the potential effectiveness of topical capsaicin in patients with nausea and vomiting due to a suspected CHS exacerbation. Methods: This was a double‐blind, randomized placebo‐controlled pilot trial. Adults who presented with vomiting suspected to be from CHS were eligible for enrollment. We excluded pregnant women and those with resolution of symptoms. Following randomization, topical 0.1% capsaicin or placebo cream was applied to the anterior abdomen in a uniform manner. The primary outcome was the severity of nausea on a visual analog scale (VAS) of 0 to 10 cm assessed at 30 minutes. Secondary outcomes were adverse events, occurrence of posttreatment vomiting, nausea by VAS at 60 minutes, and hospital admission. Results: This pilot trial enrolled 30 patients, 17 in the capsaicin arm and 13 in the placebo arm. One patient in the capsaicin arm did not tolerate treatment due to skin irritation. Mean ± SD nausea severity at 30 minutes was 4.1 ± 2.3 cm in the capsaicin arm and 6.1 ± 3.3 cm in the placebo arm (difference = −2.0 cm, 95% confidence interval [CI] = 0.2 to −4.2 cm). At 60 minutes, mean ± SD nausea severity was 3.2 ± 3.2 cm versus 6.4 ± 2.8 cm (difference = −3.2 cm, 95% CI = −0.9 to −5.4 cm). The percent reduction in nausea at 60 minutes from baseline was 46.0% in the capsaicin arm and 24.9% in the placebo arm (difference = 21.1%, 95% CI = −5.6% to 47.9%). A higher proportion of capsaicin group patients (29.4% vs. 0%) had complete resolution of nausea (relative risk = 3.4, 95% CI = 1.6 to 7.1). Conclusion: In this pilot trial, the application of topical capsaicin cream was associated with a significant reduction in nausea at 60 minutes but not at 30 minutes and provided more complete relief of nausea.